Grand theories and everyday beliefs science, philosophy, and their histories - Matson, Wallace I. (New York : Oxford University Press, 2011)
This unconventional book by a distinguished historian of philosophy tells the story of how humans became rational beings.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Keywords: Knowledge, Theory of; Evolutionary psychology; Belief and doubt; Philosophy -- History; Science -- History